2021
DOI: 10.1186/s13690-021-00623-2
|View full text |Cite
|
Sign up to set email alerts
|

New hepatitis C virus infection, re-infection and associated risk behaviour in male Irish prisoners: a cohort study, 2019

Abstract: Background Prisoners are recognised as a high-risk population and prisons as high-risk locations for the transmission of hepatitis c virus (HCV) infection. Injecting drug use (IDU) is the main driver of HCV infection in prisoners and harm reduction services are often suboptimal in prison settings. HCV prevalence and incident data in prisoners is incomplete which impacts the public health opportunity that incarceration provides in identifying, treating and preventing HCV infection. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…This study indicates that having a body tattoo is an important risk factor for both HBV and HCV infections. Similar findings of a significant association between having a body tattoo and HBV or HCV infections have been documented by other investigators as well [ 25 , 43 , 56 , 60 ]. Tattooing in prisons often involves the use of unsterile equipment, which poses a potential risk for the transmission of blood-borne infections [ 61 ].…”
Section: Discussionsupporting
confidence: 90%
“…This study indicates that having a body tattoo is an important risk factor for both HBV and HCV infections. Similar findings of a significant association between having a body tattoo and HBV or HCV infections have been documented by other investigators as well [ 25 , 43 , 56 , 60 ]. Tattooing in prisons often involves the use of unsterile equipment, which poses a potential risk for the transmission of blood-borne infections [ 61 ].…”
Section: Discussionsupporting
confidence: 90%
“…The hypoxia-related risk signature consists of eight hypoxia-related genes, including LDHA, DCN, PGK1, PFKP, FBP1, LOX, ENO3, and CXCR4. LDHA is an enzyme that catalyzes the mutual conversion of pyruvate and lactic acid, as well as promotes invasion, metastasis, nest loss, and apoptosis resistance in various cancers ( Cheng et al, 2021 ; Crowley et al, 2021 ; Gupta et al, 2021 ). Multiple studies have suggested that DCN can suppress lung cancer progression by blocking receptor tyrosine kinases ( Horvath et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most available prison-based cohort studies evaluating HCV incidence are old or limited by small study population size, or short follow-up. [7][8][9][10][11] The Surveillance and Treatment of Prisoners with hepatitis C (SToP-C) study evaluated the feasibility and effectiveness of direct-acting antiviral (DAA) treatment scale-up in prisons, and demonstrated a significant reduction in HCV incidence in the period following DAA treatment scale-up. 12 The present analysis evaluated the overall HCV incidence in SToP-C prisons independent of the study period, including detailed analyses of characteristics of injecting drug use associated with the risk of HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high HCV burden in the prison setting, data regarding HCV incidence are limited, 7 primarily due to logistical difficulties of implementing prospective studies with longitudinal follow‐up in prisons. Most available prison‐based cohort studies evaluating HCV incidence are old or limited by small study population size, or short follow‐up 7–11 …”
Section: Introductionmentioning
confidence: 99%